Evaluation of earth fault location algorithm in medium voltage distribution network with correction technique - N. S. B. Jamili; M. R. Adzman; S. R. A. Rahim; S. M. Zali; M. Isa; H. Hanafi (Institute of Advanced Engineering and Science, 2019)
This paper focused on studying an algorithm of earth fault location in the medium voltage distribution network. In power system network, most of the earth fault occurs is a single line to ground fault. A medium voltage distribution network with resistance earthing at the main substation and an earth fault attached along the distribution network is modeled in ATP Draw. The generated earth fault is simulated, and the voltage and current signal produced is recorded. The earth fault location algorithm is simulated and tested in MATLAB. The accuracy of the earth fault location algorithm is tested at several locations and fault resistances. A possible correction technique is explained to minimize the error. The results show an improvement fault location distance estimation with minimum error.